Luster Futuristic / Aminah Mat Taib ... [et al.] - Mat Taib, Aminah; Abdullah, Syazlin Eliza; Rosly, Rosfizatul Akma; Syed Mohd Suhaimi, Sh. Syawalina Farawahida (2000)
Luster Futuristic a partnership company which consists of 5 member al together. This company distribute and produce their own product namely ‘Kotak Limbahan’. This product is use to process food waste before flowing to the drain. This product can be use to overcome water pollution effectively. This company is situated at Jejawi, Perlis.